Derivation of human-derived iPSC line from a male adolescent with first-episode of sporadic schizophrenia - Youhui Jiang; Chuqing Zhou; Jun Zhao; Xinyi Ren; Qiang Wang; Peiyan Ni; Tao Li (Stem Cell Research)
Schizophrenia is considered to be a neurodevelopmental disorder with high heritability. In this study, peripheral blood mononuclear cells (PBMCs) were collected from a male adolescent diagnosed with first-episode of sporadic schizophrenia. Induced pluripotent stem cells (iPSCs) were generated by reprogramming using the factors OCT4, SOX2, NANOG, LIN28, c-MYC, KLF4, and SV40LT. The generated iPSC line was validated by karyotype analysis and expression of pluripotency markers. These iPSCs were capable of differentiating into derivatives of all three germ layers in vivo.